Distinct large-scale circulation patterns shaping summer heavy precipitation in the Tibetan Plateau - Yu Geng; Hong-Li Ren (Atmospheric Research, 2026)

Identification of DNA methylation based prognostic subtype and signature in epithelial ovarian cancer - Jingjing Zhou; Yuxin Chen; Wei Liu; Chao Wang; Lei Liu; Wei Geng; Linqing Chai; Dong Yang; Hongji Dai; Haixin Li; Yanrui Zhao; Kexin Chen; et al. (Human Genetics, 2026)

Multifunctional IB metal-doped SWCNT films with ultralow thermal conductivity and electron–phonon decoupling for wearable thermoelectric - Tong-Yu Li; Wen-Hao Geng; Yue-Xin Wang; Chu-dan Wang; Wenyi Wang; Qingxia Zhu; Di Zhang; Xuguo Huai; Hong-Zhang Geng (Chemical Engineering Journal, 2026)

Comparative analysis of nutritional components and metabolic profiles in spores of different Dictyophora species - Yumei Tang; Hong He; Yuru Shui; Jie Wang; Yanyin Li; Shahzad Raheel; Jinqiu Wang; Fang Geng (Food Bioscience, 2026)

Examination of growth, survival, physiological parameters, and gonad development in Pacific oysters of different ploidy under varying temperature and salinity levels - Geng Cheng; Hong Hu; Yuanxin Liang; Chengxun Xu; Qi Li (Aquaculture International, 2026)

Tibetan-Plateau heating subseasonally bursts marine heatwaves in Kuroshio Extension - Hong-Li Ren; Yu Geng; Yi Deng; Jieru Ma (Science Bulletin, 2026)

Pulse electric field-assisted preparation of soy protein isolate-based films with excellent mechanical strength and UV barrier performance - Ying Li; Xiu-Er Luo; Yu-Huan Geng; Wen-Hong Gao; Shuai Zhang; Zhong Han (Innovative Food Science & Emerging Technologies, 2026)

SIRT6 alleviates ischemic injury via orchestrating the RREB1/Snail and STC1/Smad7 signaling pathways to regulate endothelial-mesenchymal transition - Zhentao Zhang; Zheyan Fang; Shuang Zhao; Mukaddas Abdurahman; Gang Zhao; Runyang Feng; Zhenyang Guo; Xueting Yu; Hangnan Hong; Jilong Geng; Xiansu Nie; Supuya Abuduwahapi; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Stomatal width and vascular bundle anatomy govern foliar uptake and phloem transport of atmospheric Pb in wheat - Liu-Xu Feng; Xiang-Yu Li; Pei-Pei Gao; Yan Li; Gui-Li Hua; Ding-Hao Li; Li-Ping Geng; Xiao-Min Wang; Hong-J. Di; Wen-Ju Liu; Pei-Ying Xue (Journal of Hazardous Materials, 2026)

Zinc isotopic fractionation during magmatic differentiation and hydrothermal processes: implications for Li mineralization in the Jiajika granitic pegmatites, Sichuan, China - Jia-Wen Liu; Shi-Hong Tian; Xian-Lei Geng; Ying-Li Gong; Lu Chen; Shi-Qi Huang (Geochimica et Cosmochimica Acta, 2026)

Comparative study on the passion fruit essential oil microcapsules constructed from hydrophobic cellulose I/Ⅱ nanocrystals and gelatin: physicochemical and release properties - Hong He; Fengping An; Caini Li; Qingfei Dong; Qun Huang; Jinqiu Wang; Hongbo Song; Fang Geng (Food Hydrocolloids, 2026)

Variation characteristics and segment differences of urban heat exposure risk in continuous time series: A comprehensive synchronous comparison of daily and hourly scales - Junmao Zhang; Xia Yao; Meixia Lin; Tao Lin; Yuan Chen; Wenhui Li; Hongkai Geng; Yicheng Zheng; Zixu Jia; Hong Ye; Guoqin Zhang (Landscape and Urban Planning, 2026)

Preparatory Activity Indexes Motor Memory in the Motor Cortex - Xiao–Lin Shen; He–Xin Zhao; Yu–Hao Xiao; Yong–Xiang Wang; Li–Zhang Zeng; Hong–Yan Geng (Neuroscience Bulletin, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Environmental effects of Shenhu gas hydrate trial production: A perspective on carbon cycling in shallow sediments - Taiheng Lv; Cuiling Xu; Zhilei Sun; Hong Cao; Xilin Zhang; Wei Geng; Ye Chen; Sinan Xu; Dong Zhang; Yucheng Zhou; Shixing Li; Yunbao Sun; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Migration behaviour of heavy metals and vitrification characteristics in melting of municipal solid waste incineration fly ash - Quanming Li; Yajie Gao; Chao Geng; Xianfeng Shi; Hong Zhang; Cheng Chen; Yukai Wang; Jiaqi Chang; Yajie Wang; Ziyi Ding (ENGINEERING Environment, 2026)

Protein-selection mass spectrometry reveals novel RXRα-active chemicals in the Yangtze River and Yellow River - Cheng Xu; Geng Yue; Chenke Xu; Qiang Li; Xinming Shen; Kaisheng Hong; Yi Wan; Jianying Hu (Journal of Environmental Sciences, 2026)

Large-scale REE mineralization linked to intensive evolution of carbonatitic-alkaline magmas to brine-melts: Insights from Sr-Nd-Ba isotopes - Xiao-Chun Li; Geng-Xin Deng; Xiao-Yun Nan; Xue-Yin Yuan; Hong-Rui Fan; Fang Huang (Geochemistry, 2026)

PPIL1 promotes hepatocellular carcinoma progression and associates with poor prognosis - Yunyu Wu; Shuqing Jiang; Junming Yu; Hechun Lin; Saihua Zhang; Yizi Jin; Yang Su; Wenjiao Jin; Chao Ge; Qin Geng; Taoyang Chen; Jinjun Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Organic matter of PM2.5 induces cardiomyocyte toxicity by driving oxidative potential and impairing AMPK/PGC-1α-dependent mitochondrial biogenesis - Shanshan Chen; Wenqi Chen; Hong Geng; Zhiping Li; Jianwei Yue; Ruijin Li (Toxicology Letters, 2026)

Multiple Regression and Path Analysis of Morphological, Weight, and Fecundity Traits of Diploid and Tetraploid Pacific Oyster, Crassostrea gigas - Geng Cheng; Hong Hu; Yuanxin Liang; Wenlong Bi; Chengxun Xu; Haijun Liu; Qi Li (Journal of Ocean University of China, 2026)

From inhalation to systemic damage: Decoding the mechanistic cascade of silica nanoparticle-induced multi-organ toxicity - Jia-Qi Ban; Li-Hong Ao; He-Qun Gu; Yun-Geng Wei; Qiong Tian; Xiu He; Hua Zhao; Jun Li (Toxicology, 2026)

Synergistic strategy achieving high-efficiency PBAT degradation with low CO2/NH₃ emissions in composting - Linshan Wang; Shen Yang; Yuguo Geng; Qian Li; Jiazhi Gao; Yanjiao Qi; Yamin Zhao; Junyan Liu; Hong Zhang; Zifan Wang; Peer Mohamed Abdul (Journal of Environmental Chemical Engineering, 2025)

Different AOM processes driving the formation of carbonate crusts and nodules in the Okinawa Trough - Yucheng Zhou; Hong Cao; Zhilei Sun; Wei Geng; Chenhui Liu; Xilin Zhang; Cuiling Xu; Taiheng Lv; Shixing Li; Ye Chen; Xuejun Jiang; Dong Zhang; et al. (Marine and Petroleum Geology, 2025)

Climate-driven expansion of Takayama acrotrocha blooms: First outbreak along the north coast of Shandong, China linked to intense precipitation and warming - Xin Hong; Zheng-Xi Zhou; Jin-Xiu Wang; Chao Liu; Hui-Xia Geng; Yi-Jia Song; Yi-Fan Li; Fan-Zhou Kong; Qing-Chun Zhang; Ren-Cheng Yu (Environmental Pollution, 2025)

Correlation analysis between Antarctic ice shelf calving and basal melting during 2010–2020 - Mingliang Liu; Zemin Wang; Baojun Zhang; Hong Geng; Qian Li; Jiachun An (Acta Oceanologica Sinica, 2025)

Immunosuppressive role of benzo[a]pyrene exposure in prostate cancer progression - Zhijin Zhang; Wentao Zhang; Huan Wang; Haotian Chen; Hong Wang; Yang Yu; Danjing Shen; Man Pi; Yang Wu; Ming Luo; Yanyan He; Shiyu Mao; et al. (Journal of Environmental Sciences, 2025)

Multifunctional TE-Fabric based on interlayer synergy: A flexible thermoelectric fabric for thermal management and self-powered sensing - Tong-Yu Li; Wen-Hao Geng; Ze-Long Bao; Peng-Fei Qian; Yu-Long Guo; Hong-Zhang Geng (Chemical Engineering Journal, 2025)

Pectic polysaccharides from unripe and mature kiwifruit alleviate ulcerative colitis by modulating gut microbiota and restoring the intestinal barrier - Kai-Xin Jiang; Jin-Lei Geng; Qin Yuan; Jie Li; Wen Liu; Hong-Yan Liu; Yi-Chen Hu; Liang Zou; Shengpeng Wang; Ding-Tao Wu (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Sex-and stage-specific effect of prenatal exposure to organophosphate esters with children's physical growth patterns and adiposity rebound timing: Modification by breastfeeding - Xing Wang; Juan Tong; Han Li; Mengjuan Lu; Yuan Liu; Hong Gan; Yifan Wang; Menglong Geng; Xuejiao Qie; Xiulong Wu; Hui Gao; Beibei Zhu; et al. (Journal of Hazardous Materials, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Strong interannual variation of green tides in the southern Yellow Sea: Crucial factors and implications on management strategies - Yi-Fan Li; Hui-Xia Geng; Xin Hong; Fan-Zhou Kong; Ren-Cheng Yu (Marine Pollution Bulletin, 2025)

Meta-analysis of Frequency Learning Networks combined with co-depth point localization identification to screen and validate efficient preservation methods for pitaya: 1-methylcyclopropene, carvacrol and gibberellic acid - Geng Liu; Jieyu Li; Xiaoyu Hong; Ziqin Bai; Qing Tan; Chenlan Li; Qiqiao Pan; Hui Luo; Wei Xue (Postharvest Biology and Technology, 2025)

Improving in-situ spectral estimation of wetland soil organic carbon by integrating multiple optimization strategies - Hongyi Li; Jiangtao Yang; Bifeng Hu; Yibo Geng; Qian Zhu; Yongsheng Hong; Yi Lin; Jie Peng; Wenjun Ji; Songchao Chen; Zhou Shi (CATENA, 2025)

Anti-inflammatory and hepatoprotective effects of galactose-rich heteropolysaccharides from Laoshan green tea and its physicochemical properties - Shuying Lan; Rongshen Wang; Hong Gao; Mengyao Zhao; Huiting Li; Fan Liu; Rui Geng; Yuxin Wang; Xiaoxiao Liu; Chenggang Song; Wanzhong Li (Natural Product Research, 2025)

The mechanisms of salt weathering responsible for sandstone deterioration in the Yungang Grottoes, China - Xi Yang; Xiao-Wei Jiang; Kai-Gao Ouyang; Tao-Tao Ji; Yi-Fan Gao; Xiao-Hong Geng; Ran Niu; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

Advanced molecular system for accurate identification of chicken genetic resources - Yihao Zhi; Wanzhuo Geng; Shuohan Li; Xi Chen; Mohammed Kamal Challioui; Botong Chen; Dandan Wang; Zhuanjian Li; Yadong Tian; Hong Li; Badaoui Bouabid; Xiangtao Kang; et al. (Computers and Electronics in Agriculture, 2025)

Construction and application of antimicrobial ultrafiltration membranes based on electro-stimulated hollow mesoporous carbon spheres and carbon nanotubes - Ru-Yu Chang; Wen-Hao Geng; Li-Chao Jing; Jing-Yi Feng; Yue-Xin Wang; Peng-Fei Qian; Ze-Long Bao; Wenyi Wang; Di Zhang; Hong-Zhang Geng (Journal of Environmental Chemical Engineering, 2025)

Optimization of Microsatellite Multiplex PCRs for Triploidy Verification and Genetic Diversity Assessment in the Pacific Oyster, Crassostrea gigas - Huilin Zheng; Yuanxin Liang; Geng Cheng; Jianmin Zhou; Wenlong Bi; Hong Hu; Qi Li (Marine Biotechnology, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

All-purpose additive anchoring interface enables formation of stable uniform electrolyte-anode interphase for high performance aqueous Zn metal batteries - Jianxing Wang; Jiazhi Geng; Xiaolang Liu; Yuxi Yang; Shuhao Yao; Chang Hong; Huiying Li; Zhen Lu; Runming Tao; Jiyuan Liang; Shih-Yuan Lu (Chemical Engineering Journal, 2025)

Neurotensin Modulates Emotional Valence Assignment in the Basolateral Amygdala Through Neuromodulator Gain - Maimaitishalijiang Abudureheman; Yu-Hao Xiao; Li-Zang Zeng; Hong-Yan Geng (Neuroscience Bulletin, 2025)

Selenium-enriched Lactobacillus plantarum alleviate of high alkalinity-induced microbiota-gut-blood systems affect by improving the gut microbiota - Xinchi Shang; Longwu Geng; Haijun Wei; Xinghua Che; Lu Xing; Meiqi Xing; Wei Xu; Jian Hong Li (Aquaculture, 2024)

A ship motion forecasting approach based on Fourier transform, regularized Bi-LSTM and chaotic quantum adaptive WOA - Ming-Wei Li; Rui-Zhe Xu; Jing Geng; Wei-Chiang Hong; He Li (Ocean Engineering, 2024)

Circ-Bptf Ameliorates Learning and Memory Impairments via the miR-138-5p/p62 Axis in APP/PS1 Mice - Hong-Fang Wang; Yi-Bo Li; Zi-Yu Liu; Wen-Meng Xie; Qing Liu; Run-Jiao Zhang; Wen-Yu Wang; Jia-Xin Hao; Lei Wang; Dan-Dan Geng (Molecular Neurobiology, 2024)

Growth, survival and thermotolerance of diploids, triploids and tetraploids of the Fujian oyster Crassostrea angulata with normal, golden and black shell colors - Yuanxin Liang; Hong Hu; Geng Cheng; Chengxun Xu; Qi Li (Aquaculture, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

A critical review on inflammatory bowel diseases risk factors, dietary nutrients regulation and protective pathways based on gut microbiota during recent 5 years - Pengkui Xia; Tao Hou; Hong Jin; Yaqi Meng; Jing Li; Fuchao Zhan; Fang Geng; Bin Li (Critical Reviews in Food Science and Nutrition, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Magnetized bentonite modified rice straw biochar: Qualitative and quantitative analysis of Cd(II) adsorption mechanism - Shu-zhi Liu; Wei Ding; Hong-wei Zhang; Zhu-shuai Li; Ke-chun Tian; Ce Liu; Zeng-chao Geng; Chen-yang Xu (Chemosphere, 2024)

Seasonal predictability of SST anomalies and marine heatwaves over the Kuroshio extension region in the Copernicus C3S models - Chenguang Zhou; Hong-Li Ren; Yu Geng; Run Wang; Lin Wang (Ocean Modelling, 2024)

Influence of humic acid on the bioaccumulation, elimination, and toxicity of PFOS and TBBPA co-exposure in Mytilus unguiculatus Valenciennes - Qianqian Geng; Liang Zou; Hong Liu; Mengmeng Guo; Fengling Li; Xiangxiang Liu; Hanlin Qin; Xu Wang; Zhijun Tan (Science of The Total Environment, 2024)

Polyethylene microplastics induced gut microbiota dysbiosis leading to liver injury via the TLR2/NF-κB/NLRP3 pathway in mice - Ran Xu; Jing-wen Cao; Hong-li Lv; Yuan Geng; Meng-yao Guo (Science of The Total Environment, 2024)

Inert salt-assisted solvent-free synthesis of high-entropy oxide towards high-performance lithium-ion batteries - Xiaolang Liu; Runming Tao; Cheng Li; Jianxing Wang; Shuhao Yao; Chang Hong; Huiying Li; Jiazhi Geng; Jiyuan Liang (Chemical Engineering Journal, 2024)

Tumor microenvironment-activated hollow vanadium-based nanoplatform for precise therapy of lung cancer through synergistically reversing cisplatin resistance - Lang Ran; Jianmin Xiao; Weijie Zhang; Miaomiao Wang; Huan Xin; Huimin Li; Hong Hao; Maoyang Wang; Xiaofei Wang; Geng Tian; Guilong Zhang (Chemical Engineering Journal, 2024)

Geochemistry of iron and trace metals in seep carbonates of the middle Okinawa Trough impacted by hydrothermal plumes - Shuang-Shuang Qin; Mao-Xu Zhu; Tie Li; Xilin Zhang; Cuiling Xu; Hong Cao; Wei Geng; Bin Zhai; Ye Chen; Shixing Li; Zhilei Sun (Chemical Geology, 2024)

Advances in the study of silica nanoparticles in lung diseases - Li-Hong Ao; Yun-Geng Wei; Hong-Ru Tian; Hua Zhao; Jun Li; Jia-Qi Ban (Science of The Total Environment, 2024)

A green synthesis route of cyclohexanol via transesterification reaction intensified by reactive distillation technology - Zhengkun Hou; Xueli Geng; Qiuyan Ding; Hong Li; Yaocong Guo; Ting Qiu; Chen Yang; Qinglian Wang; Xin Gao (Journal of Cleaner Production, 2024)

Zinc attenuates arsenic overdose-induced brain damage via PERK/ATF6 and TLR/MyD88/NF-κB pathways - Weijun Wang; Yue Zhang; Xiren Geng; Hong Li; Xuehuan Wang; Yingzi Zhang; Hongjing Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Untargeted metabolomics analysis of non-volatile metabolites and dynamic changes of antioxidant capacity in Douchi with edible mushroom by-products - Pei-Xiu Rong; Xiao-Qin He; Mutamed Ayyash; Yi Liu; Ding-Tao Wu; Fang Geng; Hua-Bin Li; Siew Bee Ng; Hong-Yan Liu; Ren-You Gan (Food Chemistry, 2024)

Molecular catalysts with electronic axial stretching for high-performance lean-oxygen seawater batteries - Quanjun Tang; Liang Bai; Chen Zhang; Rongwei Meng; Li Wang; Chuannan Geng; Yong Guo; Feifei Wang; Yingxin Liu; Guisheng Song; Guowei Ling; Haitao Sun; et al. (Science Bulletin, 2023)

Prevalence of paratuberculosis in cattle in China: A systematic review and meta-analysis - Na Lu; Ya-Ling Niu; Yang Song; Dan-Dan Zhang; Jing Jiang; Jiaqi Wei; Hong-Li Geng; Hongwei Cao (Preventive Veterinary Medicine, 2023)

Associating phthalate exposure during pregnancy with preschooler's FMI, ABSI and BRI trajectories via putative mechanism pathways - Hui Gao; Yi Zhang; Li-wen Chen; Hong Gan; Meng-juan Lu; Binbin Huang; Juan Tong; Meng-long Geng; Kun Huang; Cheng Zhang; Bei-bei Zhu; Shan-shan Shao; et al. (Chemosphere, 2023)

An ephemeral increase in organic carbon, ion ratios, and heavy metal-containing fine particles was screened in a maritime demarcation zone between North and South Korea - Hong Geng; Xiaolu Li; Hae-Jin Jung; Seok-Jun Seo; Dong-Hee Jung; Jihoon Park; Yong-Jae Lim; Joon Young Ahn; Li Wu; Hanjin Yoo; Chul-Un Ro (Atmospheric Environment, 2023)

Maternal exposure to cetylpyridinium chloride impairs oogenesis by causing mitochondria disorder in neonates - Ronglu Liu; Xinyi Mu; Rufei Gao; Yanqing Geng; Yan Zhang; Xuemei Chen; Xin Yin; Hong Wang; Fangfang Li; Junlin He (Environmental Toxicology and Pharmacology, 2023)

Computer-controlled scanning electron microscope: Methodologies and application scenarios in atmospheric particle research - Wenjun Li; Longyi Shao; Hong Geng; Gary S. Casuccio; Jian Gao (Science of The Total Environment, 2023)

Assessment of heavy metals leachability characteristics and associated risk in typical acid mine drainage (AMD)-contaminated river sediments from North China - Xianyun Zheng; Yanchao Lu; Jingchao Xu; Hong Geng; Yuyu Li (Journal of Cleaner Production, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

Occurrence, distribution, and risk assessment of quinolone antibiotics in municipal sewage sludges throughout China - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Hazardous Materials, 2023)

Methane distribution and sea-to-air methane flux in the Dongsha area of the South China Sea - Cuiling Xu; Zhilei Sun; Qing Li; Xianrong Zhang; Xilin Zhang; Bin Zhai; Qiang Fu; Yuhai Sun; Wei Geng; Hong Cao; Ye Chen; Nengyou Wu (Continental Shelf Research, 2023)

Structural characterization of a pectic polysaccharide from laoshan green tea and its inhibitory effects on the production of NO, TNF- α and IL-6 - Fan Liu; Rongshen Wang; Ying Chen; Rui Geng; Hong Gao; Feng Wang; Xiaoxiao Liu; Wanzhong Li (Natural Product Research, 2023)

Endophytic Phthalate-degrading Bacillus subtilis N-1-gfp colonizing in soil-crop system shifted indigenous bacterial community to remove di-n-butyl phthalate - Li-Hui Liu; Jia-Yan Zhang; Guang-Xuan Tang; Yu-Hong Huang; Xiang-Qing Xie; Jun Geng; Hui-Xiong Lü; Hui Li; Yan-Wen Li; Ce-Hui Mo; Hai-Ming Zhao; Quan-Ying Cai (Journal of Hazardous Materials, 2023)

Improving flavor, bioactivity, and changing metabolic profiles of goji juice by selected lactic acid bacteria fermentation - Wenhui Duan; Qijie Guan; Hui-Ling Zhang; Fang-Zhou Wang; Ran Lu; De-Mao Li; Yan Geng; Zheng-Hong Xu (Food Chemistry, 2023)

Seasonal modulation of mixed-layer temperature anomaly in Kuroshio–Oyashio confluence region by bimodal Kuroshio extension - Yu Geng; Hong-Li Ren; Qiang Wang (Climate Dynamics, 2023)

Transcriptome Analysis of Reciprocal Hybrids Between Crassostrea gigas and C. angulata Reveals the Potential Mechanisms Underlying Thermo-Resistant Heterosis - Gaowei Jiang; Yin Li; Geng Cheng; Kunyin Jiang; Jianmin Zhou; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Tea polyphenol and epigallocatechin gallate ameliorate hyperlipidemia via regulating liver metabolism and remodeling gut microbiota - Jia-Jia Wen; Ming-Zhi Li; Chun-Hua Chen; Tao Hong; Jing-Rui Yang; Xiao-Jun Huang; Fang Geng; Jie-Lun Hu; Shao-Ping Nie (Food Chemistry, 2023)

Prediction and significance of intra-platform shoals distribution of Changxing formation in Gaoshiti area of Sichuan Basin - Dong Wang; Hong Liu; Tong Yu; Minglong Li; Lei Tan; Kun Zhang; Chao Geng; Cong Chen (Carbonates and Evaporites, 2023)

Three-dimensional numerical study of cooling water discharge of Daya Bay Nuclear Power Plant in southern coast of China during summer - Bingxu Geng; Lingyan Lu; Qian Cao; Wen Zhou; Shiyu Li; Ding Wen; Man Hong (Frontiers in Marine Science, 2023)
The impact of thermal pollution caused by cooling water discharge of power plant on the surrounding marine ecology has been a hot issue in oceanographic research. To reveal the distribution pattern of cooling water discharge of Daya Bay Nuclear Power Plant in summer and the impact on the surrounding marine environment, this research established a high-resolution three-dimensional (3D) numerical model based on ECOMSED in the Daya Bay. The model results are consistent with the observations on the distribution of tide level and temperature. The simulated horizontal distribution of temperature rise is consistent with the distribution trend of remote sensing images. The study showed that the stratification of the Daya Bay water is stronger in summer. The cooling water mainly spreads in the surface layer, and the temperature rise in the bottom layer is not apparent. Quantitative analysis showed that around 18.8-21.6 km 2 of the area has 1°C surface temperature rises. The area of temperature rises that exceeds 2 °C is between 6.2 and 8.1 km 2 . The area of temperature rises that exceeds 4 °C is between no more than 1.2 km 2 . The area with a bottom temperature rises of 1 °C does not exceed 2.2 km 2 , and there is no area that has a bottom temperature rise over 1 °C. The tidal dynamics process influences on the dispersion of cooling water discharge from Daya Bay Nuclear Power Plant, where the influence is more significant in the spring tide period than in the neap tide period. Our findings are consistent with previous researches.

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

The source distribution and seasonal discrepancies of antibiotic resistance genes among multiple environment media in a cold megacity - Fan Meng; Shaojing Sun; Jialu Geng; Lixin Ma; Jinpan Jiang; Bo Li; Stephen Dauda Yabo; Lu Lu; Donglei Fu; Jimin Shen; Hong Qi (Journal of Cleaner Production, 2023)

Rapid identification of fish species by laser-induced breakdown spectroscopy and Raman spectroscopy coupled with machine learning methods - Lihui Ren; Ye Tian; Xiaoying Yang; Qi Wang; Leshan Wang; Xin Geng; Kaiqiang Wang; Zengfeng Du; Ying Li; Hong Lin (Food Chemistry, 2023)

Advanced layered oxide cathodes for sodium/potassium-ion batteries: Development, challenges and prospects - Zhi-Xiong Huang; Zhen-Yi Gu; Yong-Li Heng; Edison Huixiang Ang; Hong-Bo Geng; Xing-Long Wu (Chemical Engineering Journal, 2023)

Within-day variation and health risk assessment of trihalomethanes (THMs) in a chlorinated indoor swimming pool in China - Xianyun Zheng; Jingchao Xu; Ye Gao; Wanghong Li; Yimei Chen; Hong Geng; Jianwei Yue; Min Xu (Environmental Science and Pollution Research, 2022)

Experimental study on the effects of particle grading on lime-treated slurry with vacuum preloading - Hong-lei Sun; Zhen-qi Weng; Xue-yu Geng; Meng-fen Shen; Xiao-dong Pan; Li Shi; Yuan-qiang Cai (Marine Georesources & Geotechnology, 2022)

Comprehensive analysis using multiple-integrated techniques on the failure mechanism and dynamic process of a long run-out landslide: Jichang landslide case - Yiding Bao; Hong Wang; Lijun Su; Dajiang Geng; Liang Yang; Peng Shao; Yuchao Li; Ni Du (Natural Hazards, 2022)

Sweet tea ( Lithocarpus polystachyus rehd.) as a new natural source of bioactive dihydrochalcones with multiple health benefits - Ao Shang; Hong-Yan Liu; Min Luo; Yu Xia; Xiao Yang; Hang-Yu Li; Ding-Tao Wu; Quancai Sun; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Analysis of pigment cell composition, pigment content, tyrosinase content and activity of three kinds of loaches Misgurnus anguillicaudatus from Poyang Lake - Junqing Sheng; Le Guan; Bin Sheng; Shiyu Geng; Di Wu; Beijuan Hu; Zhixiong Li; Shunlong Le; Yijiang Hong (Journal of Fish Biology, 2022)
Pigment cell composition, pigment content, tyrosinase content and activity analysis were investigated on three kinds of loaches Misgurnus anguillicaudatus : big blackspot loaches (BBL), small blackspot loaches (SBL) and non‐blackspot loaches (NBL), from Poyang Lake. Results showed that there were three types of skin pigment cells, namely melanophores, xanthophores and iridophores. Melanophores in dorsum were more than those in abdomen. Melanophore cytosomes in BBL were larger than those in SBL and NBL, and melanosomes were the largest in stage four. The melanophores in dorsal skin of SBL or NBL were small cell bodies, spindle‐like and in chain distribution. There was an extremely significant difference in melanin content in BBL between the dorsum and abdomen ( P 0.01). There were no significant differences in melanin abdominal content, lutein and carotenoid contents among three kinds of loaches ( P > 0.05). In dorsal skin, tyrosinase content was the highest in BBL, and it was significantly lower in NBL than in BBL and SBL ( P 0.01). This study reveals the differences in pigment and tyrosinase content in three kinds of loaches and provides a theoretical basis for further study of the mechanism of black spot formation.

The spatiotemporal distribution and potential risk assessment of 19 phthalate acid esters in wastewater treatment plants in China - Shaojing Sun; Jimin Shen; Bo Li; Jialu Geng; Lixin Ma; Hong Qi; Anping Zhang; Zebin Zhao (Environmental Science and Pollution Research, 2021)

The GIS study on the spatial structure and visual perception of historical districts in winter cities - Li Hong; Songling Pang; Meiyun Geng; Sihan Wang (Arabian Journal of Geosciences, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

miR164-targeted TaPSK5 encodes a phytosulfokine precursor that regulates root growth and yield traits in common wheat (Triticum aestivum L.) - Yuke Geng; Chao Jian; Wu Xu; Hong Liu; Chenyang Hao; Jian Hou; Hongxia Liu; Xueyong Zhang; Tian Li (Plant Molecular Biology, 2020)

Three-dimensional numerical modeling of water distribution tunnels in karst area - Xiao-dong Pan; Yu-chao Fang; Yong Lai; Hong-lei Sun; Yuan-qiang Cai; Li Shi; Xue-yu Geng (Arabian Journal of Geosciences, 2020)

Topographic controls on the annual runoff coefficient and implications for landscape evolution across semiarid Qilian Mountains, NE Tibetan Plateau - Shun Cai; Hao-peng Geng; Bao-tian Pan; Yang Hong; Li-ping Chen (Journal of Mountain Science, 2020)

Aircraft Measurement of Chemical Characteristics of PM2.5 over the Yangtze River Area in China - Lihong Ren; Renjian Zhang; Xiaoyang Yang; Chunmei Geng; Wei Wang; Shiro Hatakeyama; Hong Li; Wen Yang; Zhipeng Bai; Akinori Takami; Hongjie Liu; Jianhua Chen (Aerosol Science and Engineering, 2018)

Global patterns of dead fine root stocks in forest ecosystems - Cunguo Wang; Zhao Chen; Ivano Brunner; Zhen Zhang; Xianjin Zhu; Jiandong Li; Hong Yin; Wei Guo; Tianhong Zhao; Xingbo Zheng; Shuqi Wang; Zhenzhen Geng; et al. (Journal of Biogeography, 2018)
Aim Dead fine roots are crucial components of the carbon cycle in global forest ecosystems. Despite their importance, knowledge concerning geographical patterns of dead fine root pools (necromass) and factors influencing their dynamics remain scarce across the globe. Location Global. Methods We analysed 136 published case studies covering 169 forest sites located throughout the world to identify broad patterns of necromass and biomass (living fine root pools) and to determine the responses to climate, edaphic gradients and stand properties. Results W‐shaped pattern of forest necromass with latitude, from the Southern Hemisphere via the equator to the Northern Hemisphere, was observed. Specifically, more necromass was found at both low (tropical forests) and high latitudes (boreal forests), whereas less necromass was found at mid latitudes (temperate forests), which is in line with patterns of carbon stocks in soils at the global scale. Broad‐leaf forests had greater necromass than needle‐leaf forests, and fine root necromass of the two forest types showed opposing trends in response to shifts in mean annual precipitation and different sensitivities to changes in mean annual temperature and edaphic properties (e.g. soil carbon/nitrogen ratio and pH ). Necromass increased with soil organic layer thickness and stand age for both forest types. Main conclusions The hemispheric symmetrical necromass distribution is likely determined by changes in environmental conditions across latitudes. Different responses of dead fine roots in broad‐leaf and needle‐leaf forests may be caused by their distinct allocation and accumulation of carbon in relation to climate and to edaphic and forest characteristics at the global scale. Our results have important implications for accurate quantification and modelling of forest ecosystem carbon stocks and cycles and for assessments of their sensitivity and stability in a changing climate.

Cotton (Gossypium hirsutum) JAZ3 and SLR1 function in jasmonate and gibberellin mediated epidermal cell differentiation and elongation - Xiao-Cong Xia; Qian-Qian Hu; Wen Li; Yun Chen; Li-Hong Han; Miao Tao; Wen-Ying Wu; Xue-Bao Li; Geng-Qing Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Fine chalk dust induces inflammatory response via p38 and ERK MAPK pathway in rat lung - Yuexia Zhang; Zhenhua Yang; Yunzhu Chen; Ruijin Li; Hong Geng; Wenjuan Dong; Zongwei Cai; Chuan Dong (Environmental Science and Pollution Research, 2018)

Down-Regulation of Neuregulin1/ErbB4 Signaling in the Hippocampus Is Critical for Learning and Memory - Jia Tian; Fei Geng; Feng Gao; Yi-Hua Chen; Ji-Hong Liu; Jian-Lin Wu; Yu-Jie Lan; Yuan-Ning Zeng; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Molecular Neurobiology, 2017)

Household factors and adopting intention of battery electric vehicles: a multi-group structural equation model analysis among consumers in Jiangsu Province, China - Wenbo Li; Ruyin Long; Hong Chen; Jichao Geng (Natural Hazards, 2017)

Nuclear magnetic resonance T2 spectrum: multifractal characteristics and pore structure evaluation - Jian-Ping Yan; Xu He; Bin Geng; Qin-Hong Hu; Chun-Zhen Feng; Xiao-Pan Kou; Xing-Wen Li (Applied Geophysics, 2017)

Three new species of Boletaceae from the Heishiding Nature Reserve in Guangdong Province, China - Fang Li; Kuan Zhao; Qing-Li Deng; Ming Zhang; Christian Staehelin; Xiao-Xia Chen; Hong-Ying Chen; Geng-Shen Wang; Bing-Sheng Li (Mycological Progress, 2016)

Responses and recovery pattern of sex steroid hormones in testis of Nile tilapia (Oreochromis niloticus) exposed to sublethal concentration of methomyl - Shun Long Meng; Li Ping Qiu; Geng Dong Hu; Li Min Fan; Chao Song; Yao Zheng; Wei Wu; Jian Hong Qu; Dan Dan Li; Jia Zhang Chen; Pao Xu (Ecotoxicology, 2016)

Organic two-photon nanoparticles modulate reactive oxygen species, intracellular calcium concentration, and mitochondrial membrane potential during apoptosis of human gastric carcinoma SGC-7901 cells - Geng Chen; Shou-Ying Li; Hamid Tayyab Malik; Yu-Guang Ma; Hong Xu; Lian-Kun Sun (Biotechnology Letters, 2016)

The Kuqa late Cenozoic fold–thrust belt on the southern flank of the Tian Shan Mountains - Yue-Jun Li; Lei Wen; Hong-An Zhang; Tai-Zhu Huang; Hui-Li Li; Yuan-Yuan Shi; Qing-Long Meng; Geng-Xin Peng; Shao-Ying Huang; Qiang Zhang (International Journal of Earth Sciences, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Effects of ambient PM2.5 on pathological injury, inflammation, oxidative stress, metabolic enzyme activity, and expression of c-fos and c-jun in lungs of rats - Ruijin Li; Xiaojing Kou; Lizhi Xie; Fangqin Cheng; Hong Geng (Environmental Science and Pollution Research, 2015)

Isoprenaline induces epithelial–mesenchymal transition in gastric cancer cells - Yan-Jie Lu; Zhi-Jun Geng; Xiao-Yan Sun; Yu-Hong Li; Xiao-Bing Fu; Xiang-Yang Zhao; Bo Wei (Molecular and Cellular Biochemistry, 2015)

Effects of coarse chalk dust particles (2.5–10 μm) on respiratory burst and oxidative stress in alveolar macrophages - Yuexia Zhang; Zhenhua Yang; Yan Feng; Ruijin Li; Quanxi Zhang; Hong Geng; Chuan Dong (Environmental Science and Pollution Research, 2015)

A novel anti-TNF scFv constructed with human antibody frameworks and antagonistic peptides - Shusheng Geng; Hong Chang; Weisong Qin; Ming Lv; Yan Li; Jiannan Feng; Beifen Shen (Immunologic Research, 2015)

Preserving GABAergic interneurons in acute brain slices of mice using the N-methyl-D-glucamine-based artificial cerebrospinal fluid method - Geng Pan; Yue Li; Hong-Yan Geng; Jian-Ming Yang; Ke-Xin Li; Xiao-Ming Li (Neuroscience Bulletin, 2015)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Genomic sequence analysis of a new reassortant infectious bursal disease virus from commercial broiler flocks in central China - Pei Cui; Shi-Jie Ma; Yu-Geng Zhang; Xin-Sheng Li; Xiao-Yun Gao; Bao-An Cui; Hong-Ying Chen (Archives of Virology, 2013)

A centrifuge simulated push–pull manoeuvre with subsequent reduced +Gz tolerance - Yan Xu; Bao-Hui Li; Li-Hui Zhang; Zhao Jin; Xiao-Yang Wei; Hong Wang; San-Yuan Wu; Hai-Xia Wang; Quan Wang; Gui-Ding Yan; Lue Deng; Xi-Chen Geng (European Journal of Applied Physiology, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Synthesis and evaluation of κ-opioid receptor agonistic activity and antinociceptive effect of novel morphine analogues, 7α-phenyl-6α,14α-endo-etheno-tetrahydrothebaine with substituted o-, m- and p-amino group - Hong Qi; Wei Li; Yu Qiu; Yong-yao Cui; Jian Ma; Xiao-ling Gao; Yi-bin Zeng; Jie Yang; Yun Tang; Xing-hai Wang; Wei Sheng; Qiong Xie; et al. (Medicinal Chemistry Research, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Cell surface sialic acid inhibits Cx43 gap junction functions in constructed Hela cancer cells involving in sialylated N-cadherin - Jing Li; Lei Cheng; Li-juan Wang; Hong-chun Liu; Li Li; Xiao-lu Wang; Mei-yu Geng (Molecular and Cellular Biochemistry, 2010)

Effects of submergence on photosynthesis and growth of Pterocarya stenoptera (Chinese wingnut) seedlings in the recently-created Three Gorges Reservoir region of China - Chang-Xiao Li; Hong Wei; Yang-Hui Geng; Rebecca Schneider (Wetlands Ecology and Management, 2010)

The effects of mesenchymal stem cells on c-kit up-regulation and cell-cycle re-entry of neonatal cardiomyocytes are mediated by activation of insulin-like growth factor 1 receptor - Xi-Yong Yu; Yong-Jian Geng; Xiao-Hong Li; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yao-Hua Song; Yangxin Li (Molecular and Cellular Biochemistry, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Fatty acid profiles of muscle from large yellow croaker (Pseudosciaena crocea R.) of different age - Hong-gang Tang; Li-hong Chen; Chao-geng Xiao; Tian-xing Wu (Journal of Zhejiang University-SCIENCE B, 2009)

Genetic Differentiation of Native Sheep Populations in East and South Asia - Rongqing Geng; Hong Chang; Lanping Wang; K. Tsunoda; Zhangping Yang; Wei Sun; Dejun Ji; Yonghong Li (Biochemical Genetics, 2007)

Molecular analysis of early rice stamen development using organ-specific gene expression profiling - Xiao-Chun Lu; Hua-Qin Gong; Mo-Li Huang; Su-Lan Bai; Yang-Bo He; Xizeng Mao; Zhi Geng; Song-Gang Li; Liping Wei; Jie-Shuai Yuwen; Zhi-Hong Xu; Shu-Nong Bai (Plant Molecular Biology, 2006)